Dietary patterns in Swedish adults; results from a national dietary survey. Issue 1 (22nd October 2015) - Ax, Erika; Warensjö Lemming, Eva; Becker, Wulf; Andersson, Agneta; Lindroos, Anna Karin; Cederholm, Tommy; Sjögren, Per; Fung, Teresa T.
Abstract: Dietary patterns derived by statistical procedures is a way to identify overall dietary habits in specific populations. The aim of this study was to identify and characterise dietary patterns in Swedish adults using data from the national dietary survey Riksmaten adults 2010–11 (952 women, 788 men). Principal component analyses were used and two patterns were identified in both sexes: a healthy pattern loading positively on vegetables, fruits, fish and seafood, and vegetable oils, and negatively on refined bread and fast food, and a Swedish traditional pattern loading positively on potatoes, meat and processed meat, full-fat milk products, sweet bakery products, sweet condiments and margarine. In addition, a light-meal pattern was identified in women with positive loadings on fibre-rich bread, cheese, rice, pasta and food grain dishes, substitute products for meat and dairy products, candies and tea. The healthy pattern was positively correlated to dietary fibre ( r 0·51–0·58) and n -3 ( r 0·25–0·31) (all P <0·0001), and had a higher nutrient density of folate, vitamin D and Se. The Swedish traditional and the light-meal pattern were positively correlated to added sugar ( r 0·20–0·25) and the Swedish traditional also to SFA ( r 0·13–0·21) (all P <0·0001); both patterns were in general negatively correlated to micronutrients. Dietary pattern scores were associated with, for example, age, physical activity, education and income. In conclusion, we identified three major dietary patterns among Swedish adults. The patterns can be further used for examining the association between whole diet and health outcomes.